Perspektif Ibu Hamil dan Penyedia Layanan Antenatal terkait Peningkatan Berat Badan Ibu dan Kebutuhan Gizi Selama Kehamilan: Sistematik Review: Perspectives of Pregnant Women and Antenatal Service Providers Regarding Gestational Weight Gain and Nutritional Needs: Systematic Review - Nur Anisah Rahmawati; Eighty Mardiyan Kurniawati; Arief Wibowo; Diah Indriani; Vina Firmanty Mustofa (Amerta Nutrition, 2023)
Background: Gestational weight gain that does not follow the standards can cause long-term problems for maternal and fetal outcomes. Research has found that most pregnant women cannot achieve gestational weight gain according to health standards. Objectives: This review explores the perspectives of pregnant women and antenatal care providers regarding gestational weight gain and nutritional needs. Methods: A systematic review follows the PRISMA guidelines. Several databases were accessed, namely PubMed, Google Scholar, and ScienceDirect databases, using a combination of the following Medical Subject Heading terms and relevant keywords. The inclusion criteria applied were studies written in English, evaluating the relevant topics, providing full text, and the study was published starting in 2019-2023. Results: A total of 12 articles were reviewed. Respondents were midwives, family doctors, obstetricians, health trainers, administrative officers, and pregnant and postpartum women. The nutritional status of pregnant women studied included normal and obese pregnant women. Obstacles encountered in counseling are patient attitudes, sociocultural issues (sensitive issues), accessibility of resources, and lack of communication training with patients and across professions. Sociocultural, economic status, and interpersonal factors such as social support influence patient beliefs, attitudes, and experiences. Patients may remember their positive experiences in health facilities, but there is also a fear of discrimination they face. Conclusions: This study finds the need for training in counseling and cross-professional communication techniques to health service providers regarding gestational weight gain. Appropriate counseling increases patient comfort during pregnancy and prevents adverse effects that arise during and after pregnancy.